TNF-308 G/A polymorphism and risk of acne vulgaris: a meta-analysis. - Jian-Kang Yang (Public Library of Science (PLoS), 2014)
Background The -308 G/A polymorphism in the tumor necrosis factor (TNF) gene has been implicated in the risk of acne vulgaris, but the results are inconclusive. The present meta-analysis aimed to investigate the overall association between the -308 G/A polymorphism and acne vulgaris risk. Methods We searched in Pubmed, Embase, Web of Science and CNKI for studies evaluating the association between the -308 G/A gene polymorphism and acne vulgaris risk. Data were extracted and statistical analysis was performed using STATA 12.0 software. Results A total of five publications involving 1553 subjects (728 acne vulgaris cases and 825 controls) were included in this meta-analysis. Combined analysis revealed a significant association between this polymorphism and acne vulgaris risk under recessive model (OR = 2.73, 95% CI: 1.37-5.44, p = 0.004 for AA vs. AG + GG). Subgroup analysis by ethnicity showed that the acne vulgaris risk associated with the -308 G/A gene polymorphism was significantly elevated among Caucasians under recessive model (OR = 2.34, 95% CI: 1.13-4.86, p = 0.023). Conclusion This meta-analysis suggests that the -308 G/A polymorphism in the TNF gene contributes to acne vulgaris risk, especially in Caucasian populations. Further studies among different ethnicity populations are needed to validate these findings.